2019
DOI: 10.1128/mra.00140-19
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence of the Marine Bacterium Erythrobacter flavus Strain KJ5

Abstract: Erythrobacter flavus strain KJ5 (formerly called Erythrobacter sp. strain KJ5) is a yellowish marine bacterium that was isolated from a hard coral in the Karimunjawa Islands of Indonesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…This bacterium was first isolated from a hard coral Acropora nasuta , from the Karimunjawa Islands. The complete genome sequence of the bacterium has been reported [31], whereas E. longus (JCM6170) and E. nanhaesediminis (JCM16125) were provided by the RIKEN BRC through the National Bio-Resource Project of the MEXT, Japan.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This bacterium was first isolated from a hard coral Acropora nasuta , from the Karimunjawa Islands. The complete genome sequence of the bacterium has been reported [31], whereas E. longus (JCM6170) and E. nanhaesediminis (JCM16125) were provided by the RIKEN BRC through the National Bio-Resource Project of the MEXT, Japan.…”
Section: Methodsmentioning
confidence: 99%
“…Previous analysis by 16S rDNA sequence showed that this species has a similarity of 96% to E. flavus [30]. Recently, we have reported the complete genome sequence of this newly described bacterium [31]. In a preliminary analysis of the carotenoid composition, carotenoids, such as β -carotene and zeaxanthin, have been reported but there was no indication of the presence of bacteriochlorophylls [32].…”
Section: Introductionmentioning
confidence: 99%
“…strain KJ5 which is a symbiote organism of the coral A. nasuta , is known to have zeaxanthin and -carotene [27] . In addition, it is also known that these bacteria do not have bacteriochlorophyll, but have at least 16 types of carotenoids, including -carotene and zeaxanthin [28] . Another research on compounds in Erythrobacter sp.…”
Section: Discussionmentioning
confidence: 99%
“…Coral-associated bacteria have potential roles in carbon, nitrogen, and sulfur, and give protection to host [36], therefore it is interesting to find new bacterial isolate that demonstrate such capacity, for example bacteria that can synthesis sulfated natural product compounds, particularly carotenoid pigments. In the past five year, we succeeded to discover from Acropora nasuta a yellowish marine bacterium Erythrobacter flavus strain KJ5, which capable to metabolize sulfate into the carotenoid structure [15,37]. (c) Pure colonies of Pseudoalteromonas rubra that produces antibacterial red pigment prodigiosin [32].…”
Section: Challenges and Strategy In Getting The Isolatementioning
confidence: 99%
“…In this case, based on our experience it is worth to conduct pigment analysis thoroughly because the unknown species might contain other type of carotenoid although it has the same biosynthetic pathway as it is reported. In the case of Erythrobacter flavus strain KJ5, for example, we even conducted a whole genome sequencing prior to build a hypothesis of the possibility to find a new type of sulphate containing carotenoid [37]. To analysis the carotenoid composition, we used highperformance liquid chromatography (HPLC) coupled with diode array detector (DAD) and triple quadrupole mass spectrometry (MS/MS), because we already have identified the carotenoids from the approved species as reference compounds.…”
Section: Screening Strategy Of Carotenoid-producing Bacteriamentioning
confidence: 99%